Modern Tourism Infrastructure of The Zamin District - Ozodbek Nematov (Next Scientists International Journal JSSHRF, 2026)
This in the article Jizzakh of the province Guarantor district in the territory internal and external tourism in development important place catcher tourist base and resources scientific and practical in terms of analysis In particular, Zamin national nature garden, Zamin sanatorium and Turkestan ridge in the area natural-landscape complexes tourism potential The area is illuminated. ecological purity, unique mountain - forest landscapes, healing climate and biological diversity internal tourism in development main factor to be service what is doing based on is given. With this together, modern infrastructure, hotel economy, transport and service services development through external tourism flow increase prospects seeing Research results Guarantor the district republic on a scale large recreational and ecological tourism to the center convert opportunities shows.